The Property Market, Affordability and the Malaysian National Housing Policy - Carmelo Ferlito (Institute for Democracy and Economic Affairs (IDEAS), 2019)
Key Messages * The industry is suffering a downturn that might lead to a wider economic crisis. The negative stage experienced by the housing sector is recognizable in the increasing number of unsold units, in the declining number of transactions and in the progressive cooling down of prices. Failing to recognize this fact would lead to the risk of being unprepared for an economic downturn. * The debate on affordable housing is incomplete if it is not contextualized in the realm of the general evolution of the property market. The current discussion is strongly unbalanced toward the issue of affordability, while the property market's cyclical dynamic is disregarded; such a tendency could lead to a situation in which the country will not be equipped to face the consequences of the downturn that has already started. * With regard to the affordability issue, the present study argues that home ownership is less of a problem than what the political debate would tend to suggest: with 76.3 per cent of home ownership, Malaysia is performing better than neighbouring countries. * The affordability issue is a complex one, and looking at it simply by looking at the ratio between median house price and median income is simplistic and misleading; in order to decide what is affordable is a choice involving a trade-off between three elements: price, floor area and location. * The low-end market segment is not disregarded by the private developers because it is naturally unprofitable, but because it is artificially made unprofitable by a series of regulatory obstacles that become supply-side bottlenecks. Recommendations * In order to face a downturn in the property market, this paper suggests primarily acting to address home-owners' negative equities. In the case of the emergence of a severe mortgage crisis, loan condition modifications should be helpful in seeking to reboot homeowners' damaged balance sheets in an effort to arrest a prolonged deleveraging process and more quickly restore household demand to levels no longer dominated by negative home equity. Keep in mind that this should be an emergency measure to be implemented only in dramatic circumstances. * Fiscal discipline and strict down-payment rules are recommended. In particular, it would be important for the government to monitor quantity and quality of the expenses, being clear on how eventual deficits are financed. With reference to down-payment rules, mortgage, property insurance, and property taxes should not exceed 30 percent of income. * Redesign of the fiscal system in favour of consumption taxes rather than income taxes. A mix of GST and reduced income taxes can be studied in order to ensure a source of income for the government from one side and to orient consumer attitudes toward saving, and so support re-building the monetary funds available for investment projects. * The better way to generate affordable projects would be to remove regulatory obstacles, starting with reducing the direct involvement of government agencies in building low-cost homes. * In contrast with what is suggested by the National Housing Policy, too-strict requirements for low-cost developments (i.e. minimum size) should be avoided in order to facilitate the interaction between supply and demand, taking into account the location and size factors, and therefore allowing lower income people to move toward the economic heart of the country, supporting thus not only their housing issues but also promoting their possibilities for a higher degree of social mobility. * Disruptive entrepreneurship will play a key role in developing new technologies for making housing developments cheaper from the cost side. However, in order to emerge such kind of entrepreneurship requires freedom to react to market signals and cannot be centrally designed, because of the specific nature of entrepreneurial discovery processes. * A higher role for the rental market is expected to emerge in the future. Under this perspective, the government might consider Jacob's proposal of guaranteed-rent homes, where the central authority guarantees the loan for those developers investing in affordable projects, and partially covers the rent disbursement, in order to make the projects both affordable and economically viable. This method would have the advantage of avoiding capital expenditure from the government side, and moreover of decreasing current expenditures whenever the subsidised tenants improve their economic conditions.
Keywords: B30; B32; 330; National Housing Policy; Malaysia; Affordable Housing